(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the regulatory environment and governmental strategies supporting the growth of private entrepreneurship in Uzbekistan. It highlights the classification of business entities, initiatives aimed at shielding entrepreneurs from unwarranted inspections, and the legal assurances provided for property ownership and investment security. In conclusion, the article underscores Uzbekistan’s enhanced position in international business rankings and the favorable prospects for the advancement of private enterprise.